Let’s Talk about Language: A Review of Language‐Sensitive Research in International Management - Karhunen, Päivi; Kankaanranta, Anne; Louhiala‐Salminen, Leena; Piekkari, Rebecca (Journal of Management Studies, 2018)
AbstractThis paper explores the assumptions underlying the core concept of language used in the growing field of language‐sensitive research in international management. We reviewed 92 articles on the topic of language(s) in multinational corporations published during the period 1997‐2015, and applied a linguistic lens to uncover how these articles ‘talk about language’. The assumptions found in these articles can be grouped into three complementary categories that take a structural, functional or social practice view of language. We go beyond the review by also reflecting on the consequences that these underlying assumptions have for the study of language in multinationals. We consider the social practice view the most promising one, and propose a future research agenda for advancing it and thereby contributing to theorizing about the multinational corporation more broadly.